Implikasi Kebijakan Subsidi LPG 3 Kg terhadap Penerimaan Negara dan Keuangan Daerah: Studi Kasus Jawa Barat - Riki Satia Muharam; Budiman Rusli; Nina Karlina; Candradewini Candradewini (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
This study analyzes the fiscal implications of the 3 kg LPG subsidy policy in Indonesia, focusing on its impact on national revenue and regional finance in West Java Province. Employing a descriptive qualitative approach supported by empirical data, the research reveals that although the subsidy aims to improve social welfare by providing affordable energy access for low-income households, it also creates significant fiscal pressure on both national and regional budgets. The findings indicate that the subsidy reduces potential state revenue, narrows fiscal space, and leads to inefficiencies due to mis-targeting and distribution leakages. At the regional level, the subsidy affects budget allocations, limits fiscal flexibility, and increases administrative burdens for monitoring and implementation. The case study in West Java illustrates how the suboptimal management of the subsidy generates a trade-off between achieving social goals and maintaining fiscal sustainability. Therefore, policy reforms are needed, including digitalized distribution systems, improved beneficiary targeting, and stronger fiscal coordination between central and local governments. This research contributes to the development of more efficient and sustainable energy subsidy policies and supports the improvement of public financial governance that is transparent and accountable at both national and subnational levels.